Social cognition, psychopathological symptoms, and family functioning in a sample of inpatient adolescents using variable‐centered and person‐centered approaches. (7th September 2015) - Gambin, Malgorzata; Gambin, Tomasz; Sharp, Carla
ABSTRACT: The process of diagnosis and treatment planning for adolescents requires clinicians to integrate information about various domains of functioning especially: clinical signs and symptoms, social cognition and family functioning. In the current study we applied an integrative analytic approach to mirror case conceptualization by clinicians. Our analyses were performed on the data gathered from the 328 inpatient adolescents. We used a broad range of measures of social‐cognitive constructs, family functioning and parent‐and self‐reported psychopathology. Using a combination of variable‐based (PCA) and person‐centered (LCA) analyses we determined class membership of adolescents based on variation in social cognition, psychopathology, and family functioning. We identified five latent classes: two internalizing groups, two externalizing groups and a severe psychopathology group. Patterns of general hyperfunctioning (characterized by hypermentalizing and hypervigilance to emotional stimuli) and hypofunctioning (manifested in undermentalizing and under‐reactivity to emotional stimuli), can be observed in these groups.